2021
DOI: 10.3390/ijms22083943
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of the Relationship between Blood Donor Variability and Blood Component Quality

Abstract: While differences among donors has long challenged meeting quality standards for the production of blood components for transfusion, only recently has the molecular basis for many of these differences become understood. This review article will examine our current understanding of the molecular differences that impact the quality of red blood cells (RBC), platelets, and plasma components. Factors affecting RBC quality include cytoskeletal elements and membrane proteins associated with the oxidative response as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 143 publications
0
9
0
Order By: Relevance
“…The volume of a whole blood donation is usually 450 mL ±10%, and samples undergo leucodepletion, (often by filtration) for removing the immune cells from the blood [7]. In some cases, whole blood donations have the leukocytes removed (below the limit of 5 million per unit) followed by mixing the RBCs with an additive solution and are stored in a blood bag composed of di(2-ethylhexyl) phthalate and polyvinyl chloride (PVC) [8]. The type of treatment process favored by each blood bank is chosen based on several factors, each with advantages and disadvantages [9].…”
Section: Introductionmentioning
confidence: 99%
“…The volume of a whole blood donation is usually 450 mL ±10%, and samples undergo leucodepletion, (often by filtration) for removing the immune cells from the blood [7]. In some cases, whole blood donations have the leukocytes removed (below the limit of 5 million per unit) followed by mixing the RBCs with an additive solution and are stored in a blood bag composed of di(2-ethylhexyl) phthalate and polyvinyl chloride (PVC) [8]. The type of treatment process favored by each blood bank is chosen based on several factors, each with advantages and disadvantages [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, given no differences in the four other liver damage-associated analytes measured, the rise in AST may be more indicative of hemolysis of the human pRBCs as opposed to liver damage ( 23 ). Although the human pRBCs were used within the expiration date, preanalytical variability in human donors, such as age and storage time ( 24 ), may have made these cells susceptible to breakdown with subsequent release of AST. However, prior studies have shown that rat RBCs show decreased deformability and membrane rigidity when compared to human RBCs, which may make them more susceptible to hemolysis ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to minimize the effects of donor blood variability ( Mykhailova et al, 2020 ; Hadjesfandiari et al, 2021 ) in this study, all of the metrics described above were measured and averaged across 24 units spread into 12 compatible pools. Since a novel AS needs to be universally compatible with donated RBCs, if one RBC unit in one of the pools caused high hemolysis, the measured hemolysis value for the pool would indicate the presence of an AS incompatible with at least one of the units in the pool, screening out the incompatible AS candidate at an early stage.…”
Section: Discussionmentioning
confidence: 99%